Galactomannan and Alginate Double Coat Encapsulation of Sulfamethoxazole-Trimethoprim for Treatment for Controlled Intestinal- Targeted Drug Delivery. - Gandola, K. P.
Intracellular bacterial infections cause diseases that are hard to treat because of the anatomical barriers before the antibiotic reaches the target site and small intestine for absorption. Thus, the modulated release of the antibiotic with higher stability and drug retention needs to be achieved. Encapsulation using polymers retains the stability of drugs from the harsh environment of the stomach and delivers a drug to its intended site of release. This study aims to assess the drug release property and stability of galactomannan and alginate double coat encapsulation of SMX-TMP. The encapsulation of SMX-TMP using biopolymers was done through the extrusion method. The stability of the capsule was subjected to in vitro gastrointestinal simulation analysis and was analyzed using Fourier transform infrared spectrometer (FTIR) and scanning electron microscope (SEM) to confirm the successful encapsulation and its surface morphology. The delivery of the active drug, SMX-TMP, from the capsule was observed without significant degradation in the simulated gastric environment and disintegrates at the fasted state (pH 8) of the simulated intestinal environment, which is the target site of drug release. In vitro stability test validates the protection of SMX-TMP (encapsulated) from the gastrointestinal tract (GIT) conditions. The fingerprint of drug and encapsulating material was found to be present after drug encapsulation and intestinal disintegration. Morphological micrographs showed that the capsules were spherical that measures approximately 2.7 mm; ridges at the surface of the microcapsules were present for quick hydration and disintegration. This study reports the potential of galactomannan and alginate as candidates for encapsulating antibiotics for modulated and targeted drug delivery.
Keywords: Science -- Peridoicals; Alginate; Drug delivery; Encapsulation; Galactomannan; Sulfamethoxazole-trimethoprim.